Analisis Penggunaan Akad pada Produk Pembiayaan Multijasa pada PT. Bank SUMUT Syariah KCP Stabat - Surya Irwansyah; Anjur Perkasa Alam (Institut Syekh Abdul Halim Hasan Binjai, 2022)
This study focuses on the discussion of the implementation of the distribution of multi-service financing, the contract used in multi-service financing and analysis of the multi-service financing at PT. Bank SUMUT Syariah KCP Stabat. The research method used in this research is a descriptive qualitative research method with an empirical approach. In this study, researchers used a collection technique, namely by means of observation, interviews, and documentation. The results of the study explain that the implementation of the distribution of multi-service financing of PT. Bank SUMUT Syariah KCP Stabat to customers, namely customers who come directly to the Bank with the aim of submitting a multi-service financing application, the customer chooses which financing is desired, then fills out the financing application form provided by the Bank and is accompanied by predetermined requirements and guarantees. . If all the requirements have been met and the bank agrees to provide financing, then both parties agree to put this contract in an ijarah or kafalah financing contract and signed by both. The last stage the bank will disburse the required amount of funds through the customer's account. In practice at PT. Bank SUMUT Syariah KCP Stabat, multi-service financing using ijarah contracts and kafalah contracts. Analysis of multi-service financing products at PT. Bank SUMUT Syariah KCP Stabat are as follows: strengths, namely easy requirements, fast processing, competitive margins and profit sharing, sharia-compliant contracts. weaknesses, namely: officers in the financing department are still lacking in inviting the public, people still think that Islamic banks are the same as conventional banks and limited human resources. Opportunity is the interest of the public who want to do financing at Islamic Financial Institutions. Threat is the number of similar products offered by other conventional banks. Lack of public knowledge of PT. Bank SUMUT Syariah KCP Stabat.